2023
DOI: 10.1039/d2en00726f
|View full text |Cite
|
Sign up to set email alerts
|

Study of routine metabolism and acute toxicity of mycogenic silver nanoparticles on Palaemon pandaliformis (shrimp)

Abstract: Palaemon pandaliformis is a shrimp species considered as an important indicator of environmental condition. In this study, the toxicological effects of the mycogenic silver nanoparticles obtained using the fungus Aspergillus...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…For example, PVP, a non-ionic polymer that is highly soluble in water (Koczkur et al, 2015), is commonly used due to the absence of toxic effects reported in several biological systems (Zhao and Wang, 2012;Lacave et al, 2017). However, evidence shows that even if PVP is coating AgNP, these nanomaterials can promote harmful effects such as bioaccumulation in the small intestine and liver, embryo mortality, metabolism marker alterations in shrimps, reduction of fecundity in zebrafish, and tissue necrosis (Lacave et al, 2017;Orbea et al, 2017;Ribeiro et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…For example, PVP, a non-ionic polymer that is highly soluble in water (Koczkur et al, 2015), is commonly used due to the absence of toxic effects reported in several biological systems (Zhao and Wang, 2012;Lacave et al, 2017). However, evidence shows that even if PVP is coating AgNP, these nanomaterials can promote harmful effects such as bioaccumulation in the small intestine and liver, embryo mortality, metabolism marker alterations in shrimps, reduction of fecundity in zebrafish, and tissue necrosis (Lacave et al, 2017;Orbea et al, 2017;Ribeiro et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…For example, PVP, a non-ionic polymer that is highly soluble in water (Koczkur et al, 2015), is commonly used due to the absence of toxic effects reported in several biological systems (Zhao and Wang, 2012;Lacave et al, 2017). However, evidence shows that even if PVP is coating AgNP, these nanomaterials can promote harmful effects such as bioaccumulation in the small intestine and liver, embryo mortality, metabolism marker alterations in shrimps, reduction of fecundity in zebrafish, and tissue necrosis (Lacave et al, 2017;Orbea et al, 2017;Ribeiro et al, 2023).…”
Section: Introductionmentioning
confidence: 99%